Heat transfer phenomenon of heated cylinder at various locations in a square cavity - Mohd Ruzaini, Zakaria (2009)
In this thesis, the theory of lattice Boltzmann method is been described in first chapter. The lattice Boltzmann equation method has been found to be useful in many application involving interfacial dynamics and complex boundaries. First, the introduction of this report is described the objective of the project. This project objective is to study the plume behavior of heated cylinder at various locations in square cavity. Next, the problem statement is explained in further detailed. The problems solve using the lattice Boltzmann method theory and some flow simulation. The background of the project is relating to the lattice Boltzmann method equation that is involving the Navier-Stoke equation, the governing equation and Bhatnagar-Gross-Krook (BGK) approximation. Then, the literature will explain and described further detail about the lattice Boltzmann method. The methodology is the simulation of the isothermal and thermal of the lattice Boltzmann. The isothermal include the Poiseuille and Coutte flow. The thermal include the Porous Coutte flow. The isothermal and thermal of lattice Boltzmann equation have been derived from the Boltzmann equation by discretization in both time and phase space. The result of heated cylinder at various locations in square cavity at different Rayleigh number that has been done compute that when the Rayleigh number is increase the flow will become distorted and the plume will emerge in the enclosure. This is because of the buoyancy induced and convection become more predominant than conduction. The isotherms move upward and larger plumes exist on the top of the inner square, which gives rise to the stronger thermal gradient on the top of the enclosure. Therefore, the flow strongly imposes on the above of the enclosure, which also cause the form of a thinner thermal boundary layer in this area and develops the heat transfer.